Cigarette smoking and risk of acoustic neuromas and pituitary tumours in the Million Women Study. - Benson, V; Green, J; Pirie, K; Beral, V (2010)
BACKGROUND: The relationship between cigarette smoking and incidence of acoustic neuromas and pituitary tumours is uncertain. METHODS: We examined the relation between smoking and risk of acoustic neuromas and pituitary tumours in a prospective study of 1.2 million middle-aged women in the United Kingdom. RESULTS: Over 10.2 million person years of follow-up, 177 women were diagnosed with acoustic neuromas and 174 with pituitary tumours. Current smokers at recruitment were at significantly reduced risk of incident acoustic neuroma compared with never smokers (adjusted relative risk (RR)=0.41, 95% confidence interval (CI)=0.24-0.70, P=0.001). Past smokers did not have significantly different risk of acoustic neuroma than never smokers (RR=0.87, 95% CI=0.62-1.22, P=0.4). Smoking was not associated with incidence of pituitary tumours (RR in current vs never smokers=0.91, 95% CI=0.60-1.40, P=0.7). CONCLUSION: Women who smoke are at a significantly reduced risk of acoustic neuromas, but not of pituitary tumours, compared with never smokers. Acoustic neuromas are much rarer than the cancers that are increased among smokers.